The effect of Baby-Friendly Hospital Initiative compliance on the association between mode of birth and breastfeeding initiation in Sri Lanka - Laavanya Lokeesan; Elizabeth Martin; Rebecca Byrne; Yvette D. Miller (BMC Pregnancy and Childbirth)
Abstract Background In Sri Lanka, there is some evidence that the likelihood of breastfeeding initiation varies by exposure to Baby-Friendly Hospital Initiative [BFHI]-compliant care and mode of birth. Globally, there is some evidence that exposure to mother-baby skin-to-skin contact (BFHI Step 4) is lower in caesarean section births. Therefore, we aimed to determine how breastfeeding initiation varies by mode of birth in Sri Lanka, and the extent to which women’s exposure to BFHI practices explains any associations found. Methods A cross-sectional survey was conducted with women with a live baby across four government hospitals in Sri Lanka. Quantitative data were collected through participant interviews and extraction from medical records. Associations between BFHI practices, breastfeeding initiation, mode of birth, and women’s characteristics were assessed using binary logistic regression analysis applied in mediation and moderated mediation models. Results Women who received care compliant with Steps 4 and 6 of BFHI, regardless of their mode of birth, were more likely to initiate breastfeeding within the first hour after birth. BFHI Step 4 partially and completely mediated the effect of planned caesarean section and emergency caesarean section, respectively, on breastfeeding initiation within one hour of birth. Further, exposure to BFHI Step 6 partially mediated the effect of emergency caesarean section on breastfeeding initiation within one hour of birth. Women’s age, pre-pregnancy BMI, parity status, and ethnic group significantly influenced the relationship between planned or emergency caesarean section, exposure to Step 4 or Step 6 of BFHI, and breastfeeding initiation within one hour of birth. Specifically, being primiparous strengthened the likelihood that having a planned caesarean section decreased women’s exposure to BFHI Step 4; and having a pre-pregnancy BMI of 23–27.49 kg/m2 weakened the likelihood that planned caesarean section decreased exposure to BFHI Step 4. Conclusions Improving compliance with mother-baby skin-to-skin contact (BFHI Step 4) and no supplementation (BFHI Step 6) is critical for Sri Lankan health services to support all women to establish breastfeeding initiation within one hour of birth, as these practices attenuate the negative effect of caesarean section on breastfeeding initiation.